Association Between Coexisting Constipation and Heart Failure Readmission in Patients With Heart Failure ― A Nationwide Database Study - Okada, Akira; Michihata, Nobuaki; Morita, Kojiro; Isogai, Toshiaki; Yasunaga, Hideo; Matsui, Hiroki; Miyawaki, Atsushi (Circulation Reports, 2024)
Background: Constipation often coexists with heart failure (HF) and can cause increased blood pressure variability, which may increase the risk of repeated HF admissions. However, large-scale contemporary data regarding the prognostic effect of constipation in patients with HF are lacking.Methods and Results: We retrospectively identified 556,792 patients admitted for HF for the first time and discharged alive in the fiscal years 2016–2021 using the Japanese Diagnosis Procedure Combination database. Constipation was defined as continued use of laxatives after discharge. We examined the association between constipation and 1-year HF readmission. The prevalence of constipation was 22.0% (n=122,670), which remained stable over the 6 years. Patients with constipation were older (82.7±10.1 vs. 79.3±12.8 years), more often female (53.5% vs. 48.0%), and received medications for HF more frequently at discharge compared with those without constipation. In the multivariable Cox proportional hazards model, constipation was significantly associated with a higher incidence of 1-year HF readmission (24.0% vs. 18.6%; adjusted hazard ratio [HR] 1.08; 95% confidence interval [CI] 1.06–1.10). This result was consistent with the result from the Fine-Gray model accounting for competing risk of death (subdistribution HR 1.08; 95% CI 1.06–1.09).Conclusions: Constipation was associated with a higher risk of HF readmission after the first episode of HF hospitalization. Given the detrimental effect of constipation, further efforts are warranted to decrease constipation-related risk in patients with HF.